Pedagogical foundations of teaching based on modern approaches in history classes - Usmonaliyeva Risolat Umaraliyevna (Genius Journals, 2022)
This article provides information on the pedagogical foundations of teaching history classes based on modern approaches
Keywords: History; teaching methodology; knowledge; professional activity